Peltier And Seebeck Efficacy Of Hot And Cold Air System For Portable O-Ref (Oven & Refrigerator) Application - Mohamad Haniff , Harun; Khalil Azha, Mohd Annuar; Mohd Firdaus, Mohd Ab Halim; Mohd Hanif, Che Hasan; Mohd Shahrieel, Mohd Aras; Muhamad Faizal, Yaakub (Centre for Advanced Research on Energy, 2016)
The main motivation in using Peltier Module is due to the uniqueness of producing hot and cold air at the same time besides able to generate electricity using Seebeck Effect. The generating system theoretically can recycle the heat loss to produce additional electricity for other usage. The efficacy of this system tested using two types of experimental using Peltier and Seebeck Effect. Both experimental is conducted using 3 specific volumes; 1) 1000cm3; 2) 4000cm3; and 3) 9000cm3. As a result, temperature for heating and cooling systems achieve around 14 – 56oC while the voltage generated around 12V in 50 minutes.